Adjunct Proceedings of the 2021 ACM International Joint Conference on Pervasive and Ubiquitous Computing and Proceedings of The 2021
DOI: 10.1145/3460418.3479371
|View full text |Cite
|
Sign up to set email alerts
|

Data Contribution Summaries for Patient Engagement in Multi-Device Health Monitoring Research

Abstract: The rapid growth in the range of data measures from wearable and stationary sensing devices has led to the adoption of multiple devices in health research. Such multi-device setups present challenges in sustaining patient engagement to capture continuous and high-quality datasets. One approach is to present health data to patients throughout the study but often occurs upon study completion. We report on preliminary insights from a feasibility study (IDEA-FAST) where multiple devices were used by 141 patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Performance expectancy . As pointed out by Rainey et al, 20 participants want to know that the devices actually work and that using them has a benefit for the study. Many devices do not have indications of whether they work.…”
Section: Discussionmentioning
confidence: 99%
“…Performance expectancy . As pointed out by Rainey et al, 20 participants want to know that the devices actually work and that using them has a benefit for the study. Many devices do not have indications of whether they work.…”
Section: Discussionmentioning
confidence: 99%
“…These data were collected between August 2020 and August 2021, therefore during the COVID-19 pandemic. More information can be found in [42] and a table of the participants' demographics can be found in Table 1 in the Results section.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In IDEA-FAST's feasibility study utilizing multiple sensing devices (measuring physical activity, cognition and other health metrics), a summary of health data was provided back to patients at different time points during the study. To understand the importance of returning data and the best mechanisms to do so, the study explored patients' perceived benefits of access to data, as well as use and interpretability of the data 50 . The preliminary findings suggested that patients reported using the information to monitor their health and performance, and felt confident about their adherence to the devices, which also fostered communications with clinicians.…”
Section: Establishing Dht Acceptability and Feasibility Through Real-...mentioning
confidence: 99%